Professional development training on cataloging at the University Wisconsin-Madison Memorial Library, USA - Shurshenova, Aigerim (NU Library, 2016)
This presentation provides an overview of classes on cataloging in UW-Madison Libraries and gives the most important things about cataloging in general and how UW catalogers work with bibliographical records using Integrated Library System (ILS) and other cataloging tools.
Keywords: cataloging; Memorial library; Alma; Cataloging tools; RDA; Research Subject Categories::SOCIAL SCIENCES::Other social sciences::Library and information science